The Effectiveness of the Use of the Dysmenorrhea e-booklet on Increasing Knowledge of SMAN 28 Tangerang Students in the Covid-19 Era - Dyah Woro Kartiko Kusumo Wardani; Ni Nyoman Sri Artina Dewi; Dewi Novitasari Suhaid (Journal of Midwifery, 2021)
Dysmenorrhea is a condition where pain occurs before, during and after menstruation. The most common cause of dysmenorrhea is hormonal factors. The incidence of dysmenorrhea worldwide is quite high, and Indonesian adolescents experiencing dysmenorrhea reach 43%-93%. The impact of dysmenorrhea on adolescents is the disruption of activities and a decrease in academic achievement due to lack of concentration and frequent absence of students from school. Lack of knowledge related to dysmenorrhea makes adolescents less precise in carrying out treatment; it can be seen from the number of adolescents who take anti-pain drugs to reduce dysmenorrhea pain which can cause side effects. Treatment of dysmenorrhea in addition to pharmacological can use non-pharmacological treatment.The purpose of this study was to see the effect of using dysmenorrhea e-booklets on increasing knowledge of SMAN 28 Tangerang students in the Covid-19 Pandemic Era.This pre-experiment research using a questionnaire. The research design used a One Group Design Pretest-Postest research design. The research sample was all 10th grade students of SMAN 28 Tangerang. Sampling technique was carried out using accidental sampling. The effectiveness of the dysmenorrhea e-booklet in increasing the knowledge of SMAN 28 Tangerang students was analyzed using the Wilcoxon test and obtained a significance value (sig) of 0.000 (p<0.05). The p value <0.05 indicated a significant difference between the score before being given the e-booklet and the score after given the e-booklet. Therefore, it can be concluded that the provision of dysmenorrhea e-booklets is effective in increasing respondents' knowledge about dysmenorrhea in the Covid-19 era.